(untitled) (Al-Academy, 2023)
Traditional programs and the tedious and financially costly processes they require are no longer the best choice for content makers. The continuous development and development have led to the emergence of competitive software that offers capabilities that are more suitable for aesthetic needs, as it breaks down stereotypical frameworks from the familiar to the unfamiliar to be more suitable for graphic subjects in terms of dealing with the requirements of the digital content industry. Video for communication platforms, as it has more advantages than traditional software and the flexibility and high quality it offers at the level of the final product, All of this contributed to supplementing the image with aesthetic employments with data that meets ambition and moves away from monotony due to its close connection to society and lifestyle. Cap Cut is one of the most important developed programs that benefit digital video content makers and short film makers on the Internet due to its visual capabilities that enhance the expressive aspects of production processes. Meaning and finding unconventional formulations at the level of digital effects that are constantly developed and updated to enrich the image and make it aesthetically superior through the creative employment of the work maker.